PERANCANGAN MESIN PENGHANCUR SAMPAH ORGANIK PADAT PERKOTAAN - Nada, Made; Tika, Wayan; Arda, Gede (Agrotekno, 2012)
Handling municipal garbage still becomes an ever ending problem. One way to tackle this problem is to utilize the garbage as organic fertilizer. The most promising technology in converting aerobically this rubbish to organic fertilizer is known as open windrow, but the success of implementing this technology is depended upon particle size of the garbage. So, chopping machine is needed to reduce it into a homogeneous size and constructing a chopping machine became the objective of the research. Tests on physical of the machine and its performance indicated that the designed machine was better than the machine that has already been available in the field. The size of chopped garbage was relatively homogeneous and its value was 10% better than that yielded form the older machine.
Keywords: municipal garbage, organic fertilizer, open windrow, chopping machine